A Mechanically Reliable Transparent Antifogging Coating on Polymeric Lenses. Issue 4 (19th December 2021) - Sun, Ye; Rawat, Rajdeep Singh; Chen, Zhong
Abstract: Polymeric lenses have been increasingly used to replace glass lenses due to advantages of light weight, high refractive index, and ease of making into complicated shapes. However, a severe constraint to their wider application lies with their intrinsic weakness in hardness that can lead to mechanical damages by abrasion. During service, fogging remains another unsolved challenge to optical lenses, which may significantly reduce the users' visibility or even cause accident. Therefore, it is imperative to develop mechanically reliable and transparent antifogging coating on polymeric lenses. In this work, a two‐step protocol is developed comprising a room‐temperature oxygen plasma treatment of polymer substrate followed by antifogging silica thin film deposition using pulsed laser deposition (PLD). The oxygen plasma treatment modifies the surface chemistry to allow a strong adhesion between the polymer substrate and the silica coating. Due to the porous nature of the PLD deposited nanosilica film, the coating also displays an antireflection effect. This mechanically reliable and highly transparent superhydrophilic silica coating opens great opportunity for the eyewear and high precision optics industries. Abstract : A room‐temperature facile process is developed successfully that modifies the surface of polymeric materials to endow it with excellent antifogging and antireflection properties. The as‐prepared coating is mechanically robust and durable, making it one step closer to practical applications in the eyewear and polymer optics industry.